Purification and Initial Characterization of 3-Hydroxybenzoate 6-Hydroxylase From a Halophilic Martelella Strain AD-3 - Chen, Xin; Tang, Hongzhi; Liu, Yongdi; Xu, Ping; Xue, Yong; Lin, Kuangfei; Cui, Changzheng (Frontiers in Microbiology, 2018)
3-Hydroxybenzoate 6-hydroxylase, an NADH-dependent flavoprotein, can convert 3-hydroxybenzoate which is an important intermediate in the biodegradation of many aromatic hydrocarbons. 3-Hydroxybenzoate is metabolized by entering the TCA cycle through the gentisate pathway. We found a putative 3HB6H gene from a cluster that potentially encodes for gentisic acid degradation from a halophilic Martelella sp. strain AD-3. The corresponding protein was expressed with an N-terminal his-tag and purified by Ni2+-nitrilotriacetic acid affinity chromatography. The protein showed an overexpressed band of about 46 kDa by SDS-PAGE, and it was also proven that the enzyme contains FAD by absorption spectroscopy and HPLC analysis. The optimal activity of 3HB6H from strain AD-3 was observed in phosphate buffer (pH 8.0) at 37°C without salinity (NaCl) and metal salts. The Km values of 3-hydroxybenzoate 6-hydroxylase were determined to be 72.6 ±10.1 μM and 104.1 ±18.2 μM for 400 μM NADH and 3-hydroxybenzoate, respectively. Site-directed mutagenesis showed that residues 305, 306 and 308 are important for FAD binding. In addition, we found that Tyr221 and Gln305 of 3HB6H from strain AD-3 are involved in substrate binding.